THE DOCTRINE OF STATE AND LAW IN THE IDEOLOGICAL AND POLITICAL DOCTRINE OF CLASSICAL CONSERVATISM - Anna Malkina; Anton Pastukhov (Вісник Харківського національного університету імені В. Н. Каразіна: Серія "Питання політології")
This research paper explicates the basic doctrines of the State and law of classical conservatism, as well as the peculiarities of understanding and existence of the idea of the State, which follows from the conservative definition of the State. The characteristic components of this political institution are the categories of law, legal consciousness, political integrity, etc. The perception of understanding the conservative theory of the origin of the state, based on the social contract theory, as a logical continuation of the organic association of people to maintain social order and political stability, is crystallising. The latter principles are also the fundamental axiological determinants of the conservative ideological and political doctrine, whose manifestor and defender is the state. The author characterises the concepts of law and law, the conceptual basis of which is reduced to the moral sphere of existence. The main objective of the existence of laws is to protect rights and freedoms, as well as their institutional representation. At the same time, the author defines the peculiarities of understanding legal consciousness and political consciousness as fundamental elements of state-building processes. In turn, their fundamental features are historical and geographical locality, identity and conceptual authenticity, which are the basis for the constitution of heterogeneous forms of political systems. The tasks and structural elements of the theory of state in the ideological and political doctrine of conservatism are analysed. The author also identifies the institutional elements of social limitation of state power in the context of conservative doctrine, which include the church and civil society.